Interdisciplinary Project at Tertiary Level: Recorded Story Read Alouds by Future English Language Teachers - Vanesa Polastri; Analía Urrutia Bustillo; Soledad Martínez (CLELEjournal, 2022)
This paper reports on an interdisciplinary project in Argentina. The project was affected by the Covid-19 pandemic, however the teacher educators turned this into an opportunity to develop student teachers' confidence in front of a camera by having them record their reading of picturebooks aloud.